STUDI KUALITATIF FAKTOR KINERJA KARYAWAN PADA PT. XYZ SELAMA MASA PANDEMI COVID-19 - Alvin Al Faruq; Hanung Eka Atmaja (Transpublika Publisher, 2022)
In the modern era of Covid-19 and the ongoing new normal modernization process, the business world is required to be more responsive to all innovations that occur in order to be able to survive, continue to develop, and achieve its goals. Therefore, the company will be able to compete with other businesses if the performance of its employees is competitive. This study aims to identify employee performance factors at PT. XYZ during the Covid-19 pandemic. This research is a qualitative descriptive study. Determination of the subject through the use of deliberately selected sampling. Interview and observation are the two main methods used in the data collection process. The findings show that in terms of leadership style, their leaders encourage them to take the initiative, and their leaders let their employees carry out tasks in a way that employees find most effective. Relations between employees in the workplace are still quite good. For example, if one employee is having a hard time, there are several other employees who care or are willing to help, and that employee is not hindered in his work. This will affect employee performance, and employees will feel more comfortable working if facilities are available. Besides, PT. XYZ shows the company's employees that they are not given any gifts or rewards in the company as part of the work motivation program they participate in.